2019
DOI: 10.1177/0305735619836269
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to pursue a career in music: The role of social constraints in university music programs

Abstract: The purpose of this study was twofold: (1) to describe university music students' perceptions of competitiveness, perfectionism, and teacher control in conservatory-style learning environments, and (2) to test a theoretical model of a network of relationships among perceptions of competitiveness, perfectionism, teacher control, quality of motivation, and intentions to pursue a career in music. Participants were undergraduate and graduate music majors from schools of music in the Midwestern United States and Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
3
23
0
2
Order By: Relevance
“…This is consistent with the career development of music and PE students in Taiwan, who typically begin training specific skills from a young age. Although they may be interested in the specific skills and have a favorable performance level, they also experience strong external environmental pressure, regulations, and requirements (Gustafsson et al, 2018; Miksza et al, 2019) that cause high external regulation. In addition, students majoring in PE and other disciplines had significantly higher amotivation scores than those majoring in art and music.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the career development of music and PE students in Taiwan, who typically begin training specific skills from a young age. Although they may be interested in the specific skills and have a favorable performance level, they also experience strong external environmental pressure, regulations, and requirements (Gustafsson et al, 2018; Miksza et al, 2019) that cause high external regulation. In addition, students majoring in PE and other disciplines had significantly higher amotivation scores than those majoring in art and music.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, expectancies for success was the strongest predictor of students’ intentions to choose a career in music performance, followed by attainment value, perceived ability, and intrinsic interest value. However, Miksza et al (2019) found that students’ socially prescribed expectations to be perfect at playing music were negatively associated with students’ intentions to pursue a career in music through autonomous motivation. In short, students’ expectancy-value beliefs toward music were found to positively influence their intentions to pursue a career in music (Jones & Parkes, 2010; Parkes & Jones, 2011, 2012), but socially imposed extreme expectancy beliefs (i.e., perfectionism) may be detrimental to students’ motivation to pursue a music career (Miksza et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Traditionally, studio teachers have been viewed as the “musical agents, the models, and the motivating forces for their students” (Campbell, 1991, p. 276) or, a participant in one research study noted, like “priest-like figures engaging in a kind of musical laying-on of hands” (Landes, 2008, p. 263) to promulgate particular technical, artistic, and pedagogical traditions. Collegiate/conservatory music students with strong career intentions may also perceive their teachers as more controlling (Miksza et al, 2021)—which the authors suggest career-minded students may tolerate or interpret positively, due to these students’ “admiration for their artist teacher” (p. 64) and the perception that such control is evidence of investment in their success. However, the relative investment teachers demonstrate can be inconsistent, as amounts of individualized feedback and attention are mitigated by teachers’ own self-interests and time divided among other students (Kim, 2008).…”
mentioning
confidence: 99%
“…Acknowledging the esteem in which many students hold their teachers, some tertiary music faculty have at times exercised levels of influence that are neither healthy nor helpful (Kim, 2008; Kogan, 1987). Furthermore, conservatory and music school environments are notoriously competitive and perfectionistic, with social comparisons embedded in the fabric of the educational experience as students prepare for performance competitions and advancement in a career with limited openings (Kim, 2008; Kogan, 1987; Miksza et al, 2021). Some collegiate/conservatory faculty have been known to attempt to motivate through negative social comparison and/or continual criticism, being products of a similar environment themselves (Kim, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation